Investigating cell-specific effects of FMRP deficiency on spiny projection neurons in a mouse model of Fragile X syndrome - Giua, Gabriele; Lassalle, Olivier; Makrini-Maleville, Leila; Valjent, Emmanuel; Chavis, Pascale; Manzoni, Olivier J. J. (Frontiers in Cellular Neuroscience, 2023)
Fragile X syndrome (FXS), the most common monogenic cause of autism and inherited intellectual disability, is caused by the mutation of a single gene, Fmr1, which encodes the Fragile X Messenger Ribonucleoprotein (FMRP). FXS patients suffer from cognitive, emotional, and social deficits compatible with dysfunction in the nucleus accumbens (NAc), a structure central to the control of social behavior. The major cell type of the NAc, spiny projection neurons (SPNs), are differentiated in two subtypes based on their expression of either dopamine D1 or D2 receptors, their connectivity, and associated behavioral functions. Understanding how the absence of FMRP differentially affects the cellular properties of SPNs is a necessary step to categorize FXS cellular endophenotypes. To address this question, we comprehensively compared the intrinsic passive and active properties of SPN subtypes identified in a novel Fmr1-/y :: Drd1a-tdTomato mouse model allowing in-situ identification of SPN subtypes in FXS mice. Although Fmr1 transcripts and their gene product, FMRP, were found in both SPNs subtypes, the results suggest cell-specific functions for Fmr1. The opposite membrane properties and action potential kinetics that normally discriminate D1- from D2-SPNs in WT mouse is either reversed or abolished in Fmr1-/y :: Drd1a-tdTomato mice. Multivariate analysis shed light on the compound effects of Fmr1 ablation by revealing how the phenotypic traits that distinguish each cell type in WT are modified in FXS. Together these data show that in Fragile X mice the normal dichotomy that characterizes NAc D1- and D2-SPNs is thrown out of balance, leading to a uniform phenotype that could underlie selected aspects of the pathology.